A energia nuclear em uma abordagem Ciência, Tecnologia e Sociedade como possibilidade de engajamento científico-social - FERREIRA, Francisca das Chagas da Silva (2023)
Nuclear energy is a subject little discussed in the classroom, although it is recommended as an important subject in official documents for basic education in the area of natural sciences. Aspects inherent to decisions about the production of nuclear energy almost always involve controversies and contradictions, which, in speeches in the school context, can promote knowledge that favors the conditions for decision-making. This research was guided by the questions: What discussions can emerge from the school context, about the implications of the use of science and technology in society, when studying nuclear energy? How to contribute to Science Technology and Society (CTS) approach actions, with the theme of nuclear energy, and promote the engagement of Basic Education students in scientific and social issues? The study aimed to analyze the perceptions of the use of science and technology in the speeches produced by students in the high school context. From this perspective, a teaching unit was created with the theme Nuclear Energy, based on the educational purposes of the STS approach, in order to highlight expanded participation mechanisms and enable students to engage in decision-making processes about science and technology. The activities of the teaching unit were applied in two classes in the 3rd year of high school, at a public school in the State of Maranhão, mediated by the researcher/teacher. The data collection instruments were a questionnaire and the proposal of an essay in the form of a simple summary, both developed in the classroom. The methodological path of the study followed the precepts of a qualitative, exploratory and descriptive approach. The students' speeches were analyzed with the theoretical and methodological support of Discourse Analysis of French origin, proposed by Eni Orlandi in Brazil. The results reveal that the students' initial perceptions about nuclear energy were directed to the historical context of nuclear accidents, with a vision focused on issues of science neutrality, based on scientific rationality. However, in the final activities, speeches from students who sought social participation were observed, with questions about the impacts triggered by science and technology on society. The participation of students in science and technology issues in Basic Education can contribute to the formation of the subjects' emancipatory process.